Imaging in benign and malignant mass lesions of the tongue - Subramanian, Kavitha; Ramachandran, Rajoo; Chandrasekharan, Anupama; Rangasami, Rajeswaran; P. M., Venkata Sai; Joseph, Santhosh (International Journal of Advances in Medicine, 2017)
Background: The purpose of this study was to determine the value of CT or MR imaging in demonstrating benign, malignant, congenital and iatrogenic mass lesions of the tongue. Although the vast majority of tongue masses are squamous cell carcinomas, a variety of unusual lesions may affect the tongue. Thus the characteristics and extent of these unusual lesions may be recognized only on cross sectional CT or MR images. In this article we describe the imaging findings of the various lingual masses, provide radio-pathological correlation and discuss the role of CT and MRI in diagnostic work-up of these uncommon lesions in clinical practice. Methods: Twenty nine patients with mass lesions in tongue were prospectively examined for a period of seven months from March to October 2014 with CT or MR imaging after physical examination. The imaging protocol includes contrast enhanced axial, coronal and sagittal images acquired with 64 slice GE VCT. MR imaging protocol includes three plane contrast-enhanced and non-contrast-enhanced T1-weighted turbo spin-echo sequences, T2-weighted turbo spin-echo sequences, T1-weighted fat saturated images (T1-FATSAT). Diffusion weighted imaging (DWI) and gradient imaging (GRE) acquired with GE 16 channel 1.5 Tesla MRI. The findings were further compared with surgical and histopathological results. Results: Among the twenty nine patients who were examined with CT or MRI six patients were found normal. The rest of the twenty three patients who had positive findings on imaging include seventeen squamous cell carcinoma (SCC), one thyroglossal duct cyst, two venous malformations, one hemangioma, one case of lipoma and macroglossia. Conclusions: Though MR is the sensitive imaging modality for tongue evaluation, CT is most commonly used in preoperative assessment and post-operative surveillance. CT and MRI provide good anatomic detail, precise delineation of the extent of mass lesions and their relation to surrounding structures. In addition, MR imaging is helpful when flow void is identified, it can further characterize the type of flow present. Angiography is valuable for delineating feeding and draining vessels and in defining the hemodynamic of vascular lesions.